2015
DOI: 10.1007/s00253-015-6585-2
|View full text |Cite
|
Sign up to set email alerts
|

Re-acclimation performance and microbial characteristics of a thermophilic biofilter for NOx removal from flue gas

Abstract: Currently, a novel chemical absorption-biological reduction (CABR) integrated process, employing Fe(II)EDTA as a solvent, is being under development to reduce the cost of NOx removal from flue gas. In this work, the NO removal profile, re-acclimation performance, and microbial characteristics in a thermophilic biofilter were investigated at the conditions typical to CABR process. The biofilter comprised of four layers of packing material with a surface area of 1200 m(2) m(-3). Experimental results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The calculation of physicochemical constants and the estimation of biokinetic parameters for the modeling refer to the Supporting Information, and the results under the typical operating conditions can be found in the Supporting Information, Table S1, Figure S1, and Table S2 10 Experimental Procedure. A thermophilic biofilter with an inner diameter of 0.08 m and a height of 0.6 m started up in our previous work 15 was used for NO absorption in this study. The volume of the packing layers was 1.5 L, and the specific surface area (a t ) of the packings was 1200 m 2 m −3 .…”
Section: ■ Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of physicochemical constants and the estimation of biokinetic parameters for the modeling refer to the Supporting Information, and the results under the typical operating conditions can be found in the Supporting Information, Table S1, Figure S1, and Table S2 10 Experimental Procedure. A thermophilic biofilter with an inner diameter of 0.08 m and a height of 0.6 m started up in our previous work 15 was used for NO absorption in this study. The volume of the packing layers was 1.5 L, and the specific surface area (a t ) of the packings was 1200 m 2 m −3 .…”
Section: ■ Model Developmentmentioning
confidence: 99%
“…It has been demonstrated that the CABR process features higher NO removal efficiency compared to the conventional biological denitrification, 11 which showed over 90% in the long term operation under the typical CABR conditions. 15 Parametric tests revealed that the gas residence time and the concentration of Fe(II)EDTA were critical to achieve a high NO removal efficiency. 15−17 It has been confirmed that the main end product of the NO reduction in the CABR system was nitrogen gas while N 2 O was an intermediate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, moving-bed biofilm reactor (MBBR) has been widely used in the fields of sulfate reduction, sulfur autotrophic denitrification, nitrification and denitrification due to its comparatively low footprint and efficient treatment performance [17,18]. The MBBR process principle is based on the basic principle of the biofilm process, making full use of the advantages of the activated sludge process and overcoming the shortcomings of the traditional activated sludge process and the fixed biofilm process.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction rate of Fe(III)EDTA was 5.17 × 10 −5 mol m −2 min −1 , which was only half of that of the bound NO 15 . Zhang et al 16 reported that during the operation of the CABR process, the total iron concentration in the recirculated solution dropped gradually in a biofilter. Based on the iron mass balance, the average iron loss in the biofilter was 0.83 M d −1 in the first 28 days in presence of 3% (v/v) oxygen 16 .…”
mentioning
confidence: 99%
“…Zhang et al 16 reported that during the operation of the CABR process, the total iron concentration in the recirculated solution dropped gradually in a biofilter. Based on the iron mass balance, the average iron loss in the biofilter was 0.83 M d −1 in the first 28 days in presence of 3% (v/v) oxygen 16 . van der Maas et al 17 also showed that 2 mM d −1 of EDTA degradation occurred during the long-term operation of NO removal in presence of 3.5–3.9% (v/v) oxygen.…”
mentioning
confidence: 99%